Involvement of HMGB1 in Resistance to Tumor Vessel-Targeted, Monoclonal Antibody-Based Immunotherapy - Vito Pistoia; Annalisa Pezzolo (Journal of Immunology Research)
High mobility group box 1 (HMGB1) is a member of the “danger associated molecular patterns” (DAMPs) than can localize in various compartments of the cell (from the nucleus to the cell surface) and subserve different functions accordingly. HMGB1 is implicated in maintenance of genomic stability, autophagy, immune regulation, and tumor growth. HMGB1-induced autophagy promotes tumor resistance to chemotherapy, as shown in different models of malignancy, for example, osteosarcoma, leukemia, and gastric cancer. To the best of our knowledge, there is virtually no information on the relationships between HMGB1 and resistance to immunotherapy. A recent study from our group has shed new light on this latter issue. We have demonstrated that targeting of tumor-derived endothelial cells with an anti-human CD31 monoclonal antibody in a human neuroblastoma model was unsuccessful due to a complex chain of events involving the participation of HMGB1. These results are discussed in detail since they provide the first evidence for a role of HMGB1 in resistance of tumor cells to monoclonal antibody-based immunotherapy.